2019
DOI: 10.1371/journal.pone.0212510
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of antibiotic resistance genes in beef cattle backgrounding environment over two years after cessation of operation

Abstract: Confined animal feeding operations can facilitate the spread of genes associated with antibiotic resistance. It is not known how cattle removal from beef cattle backgrounding operation affects the persistence of antibiotic resistance genes (ARGs) in the environment. We investigated the effect of cessation of beef cattle backgrounding operation on the persistence and distribution of ARGs in the beef cattle backgrounding environment. The study was conducted at a pasture-feedlot type beef cattle backgrounding ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…Along these lines, some years ago it was demonstrated that the use of antibiotics modifies the resistance genes present in bacterial communities (the resistome). The effects on this set of genes persist for years even in the absence of any contact with antibiotics (Agga et al, ; Johnsen et al, ; Sommer & Dantas, ). Smith et al () found that successive exposures to antibiotics create a resistance that is stable over time and that resistant strains can compete with susceptible strains even when there is no selective pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, some years ago it was demonstrated that the use of antibiotics modifies the resistance genes present in bacterial communities (the resistome). The effects on this set of genes persist for years even in the absence of any contact with antibiotics (Agga et al, ; Johnsen et al, ; Sommer & Dantas, ). Smith et al () found that successive exposures to antibiotics create a resistance that is stable over time and that resistant strains can compete with susceptible strains even when there is no selective pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance genes (ARGs), as emerging contaminants, play an important role in antibiotic resistance 6 via various mechanisms, including enzymes that degrade or modify the antibiotic, modification of cell components like cell wall and ribosomes, and finally efflux pumps that could confer multiple resistance to bacteria 7 . Numerous studies have demonstrated that ARGs and antibiotic resistant bacteria (ARB) occurred in various farm wastes like animal feces 8 10 and livestock wastewater 11 13 . Unfortunately, the land fertilization of livestock manure may introduce ARGs and pathogenic bacteria to farmland soil 14 – 16 , groundwater and surface water in the surrounding environment 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Some factors can contribute to transmission of antimicrobial-resistant bacteria and ARGs to humans, such as the contact with animals or the food chain [31]. Besides, antimicrobial-resistant bacteria that do not persist in the environment (i.e., soil and water) may transfer ARGs to resident soil bacteria [4,32]. Some of ARGs found have been intrinsically described in Gram-negative and Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%